1976
DOI: 10.3171/jns.1976.44.3.0303
|View full text |Cite
|
Sign up to set email alerts
|

Selection of patients for extra-intracranial arterial bypass surgery based on rCBF measurements

Abstract: Extracranial intracranial arterial anastomosis is gaining acceptance as a form of treatment in selected cases with ischemic cerebrovascular disease. To establish indications for this operation and to provide an objective assessment of postoperative results, regional cerebral blood flow (rCBF) studies were performed in 110 patients with cerebrovascular insufficiency considered for extra-intracranial bypass surgery. The 133Xe intracarotid injection method with 16 externally placed detectors was used for measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

1979
1979
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(15 citation statements)
references
References 14 publications
0
13
0
2
Order By: Relevance
“…From a theoretical point of view, one would assume that an increase in the rCBF would benefit mainly the ischemic region or only the ipsilateral hemisphere. In their study, Schmiedek VOL 13, No 5, SEPTEMBER-OCTOBER 1982 et al 4 found a similar regional improvement in the rCBF. A bilateral improvement in the rCBF was dem onstrated by Nakajima et al 5 in the months following an STA-MCA anastomosis; Meyer et al 21 reported similar results for their investigation of a group of patients with mild cerebral ischemia without surgical intervention.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…From a theoretical point of view, one would assume that an increase in the rCBF would benefit mainly the ischemic region or only the ipsilateral hemisphere. In their study, Schmiedek VOL 13, No 5, SEPTEMBER-OCTOBER 1982 et al 4 found a similar regional improvement in the rCBF. A bilateral improvement in the rCBF was dem onstrated by Nakajima et al 5 in the months following an STA-MCA anastomosis; Meyer et al 21 reported similar results for their investigation of a group of patients with mild cerebral ischemia without surgical intervention.…”
Section: Discussionmentioning
confidence: 56%
“…Austin et al, 2 Schmiedek et al, 4 Grubb et al 14 and Nakajima et al 5 found an im provement in the rCBF, predominantly in the region where the STA-MCA anastomosis was created. Thom as et al 15 were not able to demonstrate any changes in the rCBF.…”
Section: Discussionmentioning
confidence: 99%
“…14,24,35,121 By the end of a decade after the introduction of the STA-MCA bypass to the neurosurgical community, the selection of patients and the indications for surgery remained controversial despite attempts to refine the surgical indications based on the concept of hemodynamic insufficiency. 41,107,112 Our knowledge of the natural history of occlusive cerebrovascular disease was rather uncertain, and methods for the identification of hemodynamic cerebrovascular insufficiency were still evolving. Moreover, postoperative results had always been compared with the preoperative status in the same patients and not to the natural course of the disease in a randomized control group.…”
Section: Cerebral Vasospasm and Sahmentioning
confidence: 99%
“…An STA-MCA bypass has a patency rate of > 95%. 55,59 Other common cerebral revascularization techniques include interposition vein grafts, such as the greater saphenous vein, free arterial grafts including the radial artery, and artificial grafts such as polytetrafluoroethylene tubes.…”
Section: Present Practicesmentioning
confidence: 99%